Variations in vegetable production costs and prices received by the producer in the Federal District - Castor, Otoniel Soares (Pesquisa Agropecuaria Brasileira, 2014)
This study attempted to determine the variations in vegetable production costs and prices received by the producer in the Federal District of Brazil, in 1981, for a food basket consisting of eleven horticultural crops. To account for relative differences of each vegetable, these crops were studied by the eggregated weight method, specifically Fisher's ideal index number. The annual cost of production increase (1981) of this group of horticultural crops (137%) was greater than that of prices at the farm level (86%). Thus the producer's real profit diminished during this year.